Associations of sickness absence for pain in the low back, neck and shoulders with wider propensity to pain. (20th February 2020) - Coggon, David; Ntani, Georgia; Walker-Bone, Karen; Felli, Vanda E; Harari, Raul; Barrero, Lope H; Felknor, Sarah A; Rojas, Marianela; Cattrell, Anna; Serra, Consol; Bonzini, Matteo; Solidaki, Eleni; et al.
Abstract : Objectives: To explore the association of sickness absence ascribed to pain at specific anatomical sites with wider propensity to musculoskeletal pain. Methods: As part of the CUPID (Cultural and Psychosocial Influences on Disability) study, potential risk factors for sickness absence from musculoskeletal pain were determined for 11 922 participants from 45 occupational groups in 18 countries. After approximately 14 months, 9119 (78%) provided follow-up information about sickness in the past month because of musculoskeletal pain, including 8610 who were still in the same job. Associations with absence for pain at specific anatomical sites were assessed by logistic regression and summarised by ORs with 95% CIs. Results: 861 participants (10%) reported absence from work because of musculoskeletal pain during the month before follow-up. After allowance for potential confounders, risk of absence ascribed entirely to low back pain (n=235) increased with the number of anatomical sites other than low back that had been reported as painful in the year before baseline (ORs 1.6 to 1.7 for ≥4 vs 0 painful sites). Similarly, associations with wider propensity to pain were observed for absence attributed entirely to pain in the neck (ORs up to 2.0) and shoulders (ORs up to 3.4). Conclusions: Sickness absence for pain at specific anatomical sites is importantly associated with wider propensity to pain, the determinants of which extend beyond established risk factors such as somatising tendency and low mood. Better understanding of why some individuals are generally more prone to musculoskeletal pain might point to useful opportunities for prevention.